Multicenter prospective cohort study of the patient-reported outcome measures PRO-CTCAE and CAT EORTC QLQ-C30 in major abdominal cancer surgery (PATRONUS): a student-initiated German Medical Audit (SIGMA) Study - Mihaljevic, André Leopold; Frey, Pia-Elena; Friedrich, Mirco; Dörr-Harim, Colette; Tenckhoff, Solveig; Feißt, Manuel; Brindl, Niall; Studier-Fischer, Alexander; Kuner, Charlotte; Rahbari, Mohammad; Rahbari, Nuh Nabi; Bork, Ulrich; et al. (Annals of surgical oncology, 2021)
Background. The patient-reported outcomes (PRO) version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE) and the computerized adaptive testing (CAT) version of the EORTC quality-of-life questionnaire QLQ-C30 have been proposed as new PRO measures in oncology; however, their implementation in patients undergoing cancer surgery has not yet been evaluated.
List of collaborators: Coordinating investigator: Mihaljevic, André; steering committee, national leads: Fink, Christopher, Pia Frey, Mirco Friedrich, Alexander Leuck, Lukas Rädeker, Marius Schwab, Colette Doerr-Harim, Solveig Tenckhoff, Manuel Feißt, Sara Fatima Faqar-Uz-Zaman, Niall Brindl, Thomas Jing Zhi Tu, Alexander Studier-Fischer, Charlotte Kuner, Julia Gsenger, Clara Möhwald, Markus Prem, Henriette Von der Waydbrink, Katharina Tielking, Mohammad Rahbari, Boortz Bertram, Jens Neudecker, Linda Jörke, Lisa Findeisen, Pascal Fichtel, Richard Bigge, Rahbari Nuh, Ulrich Bork, Adele Klein, Strahin Stojanovich, Andreas A. Schnitzbauer, Samuel Vorbach, Jan Braune, Alexander Scholz, Paul Kreifels, Daniel Zell, Tim Van de Lo, Philipp Holzner, Verena Martini, Nico Hinz, Anna Ekaterina Finger, Nadia Kokaly, Ricardo Kosch, Sharlaine Yun Lan Piel, Michael Tachezy, Eva Gablenz, Obada T. Alhalabi, Svenja Sliwinski, Alexander Marx, Annette AuYeung, Christina Achilles, Fynn Betge, Jana Kühn, Karam Al Halabi, Lennart von Fritsch-Seerhausen, Lydia Beck, Marc Truant, Sophie Preuß, Stella Waider, Till Seiboldt, Anja Sander, Hannah Honecker, Svenja Seide, Dorothea Weber, Christopher Büsch, Florian Wagner, Lisa Reckmann, Anna-Maria Sonnenberg, Michael Zaczeck, Joscha Buech, Laura Luden, Marie-Pauline Autenrieb, Terbish Taivankhuu, Desiree Tröster, Simon Engster, Alexander Buia, Ernst Hanisch, Charlotte Müller-Debus, Alexander Heinrich, Hannah Rasel, Kartal Nergiz, Hauke Lang, Felix Watzka, Laura Pohl, Akiko Lucia Makabe, Anna-Maria Seckler, Blerina Misiraj, Carmel Kerem, Christian Lull, Jonas Voigt, Julian Pascal Beier, Leon Schütze, Leonhard Dreyer, Marie Therese Kleinsorge, Thao Nguyen, Thomas Thäwel, Tobias Günther, Florian Herrle, Diana Sadeghi, Anne Scheuerpflug, Antonia Apfelbeck, Sebastian Schömer Cuenca, Markus Albertsmeier, Petra Zimmermann, Viktor von Ehrlich-Treuenstätt, Alessia Kopp, Lena Schmitzer, Daniel Reim & Rebekka Schirren
Gesehen am 25.10.2023